A simple, fast, and cost-efficient protocol for ultra-sensitive ribosome profiling - Koubek, Jiří; Jetzinger, Katharina; Dror, Shiran; Irastortza-Olaziregi, Mikel; Frank, Dana; Kotan, Ilgin; Santos, Jaime; Tippmann, Frank; Lafrenz, Pascal; Kaessmann, Henrik; Amster-Choder, Orna; Bukau, Bernd; et al. (Nucleic acids research, 2025)
Ribosome profiling has become an essential tool for studying messenger RNA (mRNA) translation in cells with codon-level resolution. However, its widespread application remains hindered by the labour-intensive workflow, low efficiency, and high costs associated with sequencing sample preparation. Here, we present a new cost-effective and ultra-sensitive library preparation method that significantly advances the applicability of ribosome profiling. By implementing bead-coupled enzymatic reactions and product purifications, our approach increases both yield and throughput while maintaining high reproducibility. Demonstrating the sensitivity of the protocol, we prepared libraries from as little as 12 fmol of RNA, which expands the feasibility of ribosome profiling from minimal input samples, such as those derived from small populations, stressed cells, or patient-derived specimens. Additionally, we validate the versatility of the protocol across multiple species and demonstrate its applicability for RNA-seq library preparation. Altogether, this protocol provides a highly accessible and efficient alternative to existing ribosome profiling workflows, facilitating research in previously challenging experimental contexts.
Gesehen am 03.02.2026